2007
DOI: 10.1093/bioinformatics/btm175
|View full text |Cite
|
Sign up to set email alerts
|

Cotranslational protein folding—fact or fiction?

Abstract: We explore computationally the existence of evidence for cotranslational folding, based on large sets of experimentally determined structures in the PDB. Our perspective is that cotranslational folding is the norm, but that the effect is masked in most classes. We show that it is most evident in alpha/beta proteins, confirming recent findings. We also find mild evidence that older proteins may fold cotranslationally. A tool is provided for determining, within a protein, where cotranslation is most evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 20 publications
3
20
0
1
Order By: Relevance
“…Further analysis that considered topological accessibility (the ability of a protein to fold from a given residue as a starting point using only local contacts) found this to be more evident towards the N-terminus in the α / β class of proteins [59]. In a similar vein, Deane et al [60] developed a measure of previous contacts which assesses the extent to which the chain forms contacts with previously extruded residues. They also found that the α / β class and ancient folds [61] exhibited such evidence of cotranslation.…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis that considered topological accessibility (the ability of a protein to fold from a given residue as a starting point using only local contacts) found this to be more evident towards the N-terminus in the α / β class of proteins [59]. In a similar vein, Deane et al [60] developed a measure of previous contacts which assesses the extent to which the chain forms contacts with previously extruded residues. They also found that the α / β class and ancient folds [61] exhibited such evidence of cotranslation.…”
Section: Introductionmentioning
confidence: 99%
“…Various considerations have been put forward to explain these surface preferences of protein termini, several of them invoking co-translational protein folding [38]. In particular, Krishna and Englander [5] noted that

“ An apparent functional rationale for two-state folding, with the initial barrier being rate-limiting, is that it avoids the prolonged occupation of collapsed partially folded states that would expose proteins to unwanted intermolecular aggregation and proteolysis.

…”
Section: Resultsmentioning
confidence: 99%
“…Although the question of co-translational protein folding has been intensely studied in recent years (reviewed in [811]), the anchoring of distal parts of the protein, and the possible role of such anchoring in protein chain twisting, has not been given much attention. We now discuss the features of the peptidyl transferase reaction and the properties of ribosome-associated factors that may play essential roles in these processes.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, not only is the existence of a protein exit tunnel commonly accepted it is also well established that this tunnel possesses dynamic features [40,51] which enable it to play active roles in the sequence-specific arrest of nascent chains in response to the cellular signals [52,53] and in controlling the operational mode of the translocon at the ER membrane [54]. Fluorescence resonance energy transfer (FRET) measurements [54,55] and computational analyses [56][57][58] have indicated that some extent of protein folding may happen within the ribosome exit tunnel. In support to these findings, a crevice adjacent to the tunnel wall that can provide space for co-translational transient folding has been identified [59], thus hinting at intratunnel ribosomal chaperon activity.…”
Section: The Ribosome Tunnel: From the Ptc To The External Cellular Ementioning
confidence: 99%